Construction and demolition waste in concrete: Property of pre-molded parts for paving - Francisco, J. T.M. [UNESP]; de Souza, A. E. [UNESP]; Teixeira, S. R. [UNESP] (FapUNIFESP (SciELO), 2019)
Construction and demolition waste (CDW) production is a growing factor on a global scale and its incorrect disposal becomes an increasingly common problem in cities. It is estimated to represent, on average, 50% of the urban solid waste mass in the world. In this sense, an alternative to the destination is their reuse. In this work, the properties of interlocking concrete pieces for paving with the CDW in substitution to large aggregates were analyzed. The substitution occurred in fractions from 20 to 100 wt% of CDW in cylindrical test specimens to find the ideal substitution content, so that to prepare pre-molded concrete blocks. The piece properties obtained were analyzed according to Brazilian standards for compressive strength and water absorption. Therefore, the influence of the residue incorporation in the pieces, from the technical viewpoint, was verified. The sample that presented the best performance had a substitution of 20% of the natural aggregate by crushed CDW.
Keywords: CDW; Concrete; Construction and demolition waste; Interlocking paving